APLIKASI INFORMASI DAN PEMANDU WISATA DIGITAL SITUS - SITUS CANDI DI KABUPATEN SLEMAN BERBASIS ANDROID - , HENDRA PERMANA; , Maâun Budiyanto, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sleman is one of districts in the province of Yogyakarta Special Region which is famous for natural and cultural tourist destination. Most of the cultural and historical attractions located in this district. According to some sources, Sleman District was once the former Hindu and Buddhist kingdoms in its heyday, there are so many temples with Hindu and Buddhist cultural patterns contained in this districts. Seribu Candi application provides information about the temples located in the district of Sleman with very usefull features. This application also provides Google Map Features that can help travelers in finding the location of the temple. Besides as digital media information about the temples is located in Sleman, this application also can be an alternative which can be a tour guide for tourists who want to enjoy a rich of culture and history in Sleman. This application only need the Internet connection and GPS signals, so it is very easy to use. Turn on the GPS and Internet Connection on the android mobile smartphone, then enjoy the features of Seribu Candi application.